Application Of A Microsoft Access-Based Accounting Recording System At Naliang Club - Hendi Hendi; David Cantona (Universitas Internasional Batam, 2023)
NaLiang Club is a Small and Medium Enterprise (SME) in Batam which is engaged in the nutrition club and nutritional drinks. NaLiang Club still uses a manual accounting recording system, using Microsoft Excel. NaLiang Club is not capable to produce financial reports, so they did not know the actual profit that they had been generated. A survey and interview were conducted by the author to design a Microsoft Access-based accounting recording system for NaLiang Club. Those methods were conducted to know the SME’s business process and needs. Eight forms and reports each was available in the designed system. Those forms consist of chart of account, inventory, supplier, customer, cash transaction form, purchase form, sales form, and adjustment journal form. While the reports consist of purchase report, sales report, inventory card, general ledger, trial balance, financial position statement, profit loss statement, and cash flow statement. The implementation of this system increases the SME’s effectiveness in recording their transactions. NaLiang Club able to input the transaction activity in real time and find the transaction data easily if needed someday.